Bebidas ricas em açúcares de adição e“sintomas de asma na infância: análise nos primeiros 1000 dias de vida - Coorte Brisa, São Luís - VALE, Andressa Talícia Machado (2018)
The objective of this study was to analyze the association between intake of sugar-rich beverages in the first 1000 days of life and " child asthma traits ", exploring the direct and indirect ways of this association through the child's excess weight and via inflammation allergic reaction. It is a study involving variables in two moments of the BRISA cohort, São Luis, Brazil (n=1140): prenatal and second year of life of the children. A theoretical model with variables collected in prenatal (socioeconomic and maternal age) and in the second year (exclusive breastfeeding, child's age, BMI z-score and eosinophil count) was constructed to evaluate the association of SSB with " child asthma traits, "by modeling structural equations. The main explanatory variable was the percentage of sugar consumed from SSB (milk and non-dairy drinks) in relation to total calories. The "child asthma traits" outcome was a latent variable composed of four asthma indicators: medical diagnosis of asthma, wheezing, medical emergency due to severe wheezing and rhinitis. The highest percentage of sugar consumption from SSB was directly associated with higher values of "child asthma traits" (CP = 0.123; P = 0.043). Higher values of eosinophils were independently associated with "child asthma traits" (CP = 0.155; P = 0.021), while exclusive breastfeeding was protection against this outcome (CP = -0.151; P = 0.020). No direct or indirect effects of the child's excess weight on the child asthma traits were observed. These results suggest that increased consumption of SSB contributes to the risk of child asthma traits; being this independent association of the excess weight of the child and the eosinophilic inflammation.